2010
DOI: 10.1370/afm.1092
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Diagnostic Validity of the M-3 Checklist: A Brief, Self-Rated Screen for Depressive, Bipolar, Anxiety, and Post-Traumatic Stress Disorders in Primary Care

Abstract: PURPOSE Mood and anxiety disorders are the most common psychiatric conditions seen in primary care, yet they remain underdetected and undertreated. Screening tools can improve detection, but available instruments are limited by the number of disorders assessed. We wanted to assess the feasibility and diagnostic validity of the My Mood Monitor (M-3) checklist, a new, 1-page, patient-rated, 27-item tool developed to screen for multiple psychiatric disorders in primary care. METHODSWe enrolled a sample of 647 con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 53 publications
1
62
1
1
Order By: Relevance
“…No scale was difficult to administer, and even the longest could be completed by the vast majority of patients prior to their appointment. 72 Prevalence of PTSD Prevalence rates ascertained from gold standard diagnostic interviews for the 20 patient samples included in this report that contained information about prevalence range from 5% in a community primary care sample 73 to 35% in a sample of women receiving care at Veterans Health Administration facilities. 58 Based on diagnostic interviews, the random-effects summary estimate for prevalence of PTSD was 13.5% (95% CI, 5.0%-35.5%) in primary care studies, 58 We conducted 3 sensitivity analyses.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…No scale was difficult to administer, and even the longest could be completed by the vast majority of patients prior to their appointment. 72 Prevalence of PTSD Prevalence rates ascertained from gold standard diagnostic interviews for the 20 patient samples included in this report that contained information about prevalence range from 5% in a community primary care sample 73 to 35% in a sample of women receiving care at Veterans Health Administration facilities. 58 Based on diagnostic interviews, the random-effects summary estimate for prevalence of PTSD was 13.5% (95% CI, 5.0%-35.5%) in primary care studies, 58 We conducted 3 sensitivity analyses.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…72 Both patients and physicians felt that screening facilitated discussion of mental health issues in the subsequent primary care encounter, and 80% of primary care physicians reported that the screen was helpful in interactions with their patients. 72 …”
Section: Other Outcomesmentioning
confidence: 99%
“…Gaynes et al (2010) tested the My Mood Monitor (M-3) checklist, a patient-rated 27-item tool (Gaynes et al 2010). Using a sample of 647 consecutive primary care, the M-3 was examined against major depression, bipolar disorder, any anxiety disorder and post-traumatic stress disorder (PTSD) using the MINI.…”
Section: Multi-domain Screeningmentioning
confidence: 99%
“…In a related comment on a different article, 9 an experienced measure developer 10 lauds the elegance and practicality of a parsimonious new instrument that screens for 4 common mental health disorders.…”
Section: Depression Pain and Talking With Patientsmentioning
confidence: 99%